Effect of Positive End-Expiratory Pressure on Central Venous Pressure in Patients under Mechanical Ventilation - Majid Shojaee; Anita Sabzghabaei; Hossein Alimohammadi; Hojjat Derakhshanfar; Afshin Amini; Bahareh Esmailzadeh (Archives of Academic Emergency Medicine, 2018)
Introduction: Finding the probable governing pattern of PEEP and CVP changes is an area of interest for in-charge physicians and researchers. Therefore, the present study was designed with the aim of evaluating the relationship between the mentioned pressures. Methods: In this quasi-experimental study, patients under mechanical ventilation were evaluated with the aim of assessing the effect of PEEP change on CVP. Non-trauma patients, over 18 years of age, who were under mechanical ventilation and had stable hemodynamics, with inserted CV line were entered. After gathering demographic data, patients underwent 0, 5, and 10 cmH2O PEEPs and the respective CVPs of the mentioned points were recorded. The relationship of CVP and PEEP in different cut points were measured using SPSS 21.0 statistical software. Results: 60 patients with the mean age of 73.95 ± 11.58 years were evaluated (68.3% male). The most frequent cause of ICU admission was sepsis with 45.0%. 5 cmH2O increase in PEEP led to 2.47 ± 1.53 mean difference in CVP level. If the PEEP baseline is 0 at the time of 5 cmH2O increase, it leads to a higher raise in CVP compared to when the baseline is 5 cmH2O (2.47 ± 1.53 vs. 1.57 ± 1.07; p = 0.039). The relationship between CVP and 5 cmH2O (p = 0.279), and 10 cmH2O (p = 0.292) PEEP changes were not dependent on the baseline level of CVP. Conclusion: The findings of this study revealed the direct relationship between PEEP and CVP. Approximately, a 5 cmH2O increase in PEEP will be associated with about 2.5 cmH2O raise in CVP. When applying a 5 cmH2O PEEP increase, if the baseline PEEP is 0, it leads to a significantly higher raise in CVP compared to when it is 5 cmH2O (2.5 vs. 1.6). It seems that sex, history of cardiac failure, baseline CVP level, and hypertension do not have a significant effect in this regard.